Analisis Kesalahan Konseptual dan Prosedural Dalam Menyelesaikan Soal Matematika Materi Penerapan Turunan Fungsi Aljabar Ditinjau dari Gaya Kognitif Siswa di SMA Negeri 1 Gunungsari - Nurhasanah; Sudi Prayitno; Nurul Hikmah; Sri Subarinah (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
The purpose of the research is to identify the conceptual and procedural error of eleventh grade students in solving problems in the Applications of Derivatives of Algebraic Functions based on Cognitive Style. The subjects of this research are eleventh grade students of SMA Negeri 1 Gunungsari. The four selected subjects consist of two field independent students and two field dependent students. This research is included in the type of descriptive qualitative research. Data collection techniques were carried out in three stages, namely the GEFT test, a written test about the description of Mathematics for the application of Algebraic Function Derivatives, and interviews. The result of this study shows that the field independent students committed one conceptual error and four procedural errors with different indicators. Meanwhile the field dependent students committed three conceptual errors and three procedural errors with different indicators. The differences between the field independent and field dependent students error are be able to know based on the error type. The field independent students tend to make procedural errors. Meanwhile the field dependent students tend to make conceptual errors.